Zinc-Loaded Black Phosphorus Multifunctional Nanodelivery System Combined With Photothermal Therapy Have the Potential to Treat Prostate Cancer Patients Infected With COVID-19 - Li, Linfeng; Zhou, Baotong; Xu, Haoyang; Shi, Hailin; Gao, Li; Ge, Bo (Frontiers in Endocrinology, 2022)
Since 2019, coronavirus disease 2019 (COVID-19) has swept the world and become a new virus  threatening the health of all mankind.The survey found that prostate cancer accounts for one in three male cancer patients infected with COVID-19. This undoubtedly makes prostate cancer patients face a more difficult situation.Prostate cancer is the second most harmful malignant tumor in men because of its insidious onset, easy metastasis, and easy development into castration-resistant prostate cancer even after treatment. Due to its high immunogenicity and a small number of specific infiltrating T cells with tumor-associated antigens in the tissue, it is difficult to obtain a good therapeutic effect with immune checkpoint blocking therapy alone. Therefore, in the current study, we developed a platform carrying Doxorubicin (DOX)-loaded black phosphate nanometer combined with photothermal therapy (PTT) and found this drug combination stimulated the immungentic cell death (ICD) process in PC-3 cells and DC maturation.More importantly, zinc ions have a good immunomodulatory function against infectious diseases, and can improve the killing ability of the nanosystem against prostate cancer cells.The introduction of Aptamer(APT) enhances the targeting of the entire nanomedicine. We hope that this excellent combination will lead to effective treatment strategies for prostate cancer patients infected with COVID-19.